DIMINISHED IMPACT ATTENUATION PROPERTIES OF TAEKWONDO AND BOXING HEADGEAR. Issue 7 (11th March 2014) - Pieter, W; O'Sullivan, D; Fife, G
Abstract : Background: Only one study reported the impact attenuation of taekwondo headgear. Although Olympic boxing has discontinued the use of head protectors, similarities in designs are suggested to provide a framework for improving taekwondo helmets as a previous report determined poor testing results. Objective: To assess attenuation of taekwondo and boxing headgear. Design: Between-groups. Setting: Impact biomechanics laboratory. Participants: Helmets approved by the World Taekwondo Federation and those by the International Boxing Association. Risk Factor assessement: A standardized (ASTM F-2397) martial arts headgear striker was used to impart impacts to a 50 th Percentile Male Hybrid III Dummy (Hybrid III) head and neck complex. All impacts were imparted with a terminal striking velocity of 5.0 m/s (max-min=5.15–4.75 m/s). Each headgear model (boxing: Adidas and Green Hills; taekwondo: Adidas and Nike) were fitted to the Hybrid III and impacted a total of 60 times to the left side of the headgear. Main outcome measurements: Resultant linear acceleration (RLA). Results: There was a significant difference in RLA between helmets (eta 2 =0.963, 95% CI: 0.881–0.987). Pairwise comparisons showed differences between the taekwondo Nike (129.48±8.18g) and boxing Green Hills helmets (109.48±10.11g) (d=2.19, 95% CI: –4.98–11.05). The boxing Adidas helmet (75.42±9.99g) recorded a higher RLA than its taekwondo counterpart (d=2.09, 95% CI: −6.67–5.82). Conclusions: Both boxing and taekwondo helmets have a limited lifespan.